The Otherness and the Legal Symbolism of the Gestures of Treading in the Motives of Discalciation, Removed Shoes, and Monosandalism in Early Netherlandish and German Art - Rogov, Mikhail A. (Actual Problems of Theory and History of Art, 2018)
This paper is devoted to the main groups of iconographical motifs of removed shoes, discalceation, and monosandalism in Early Netherlandish and German art and their relation to the gestures of treading. Firstly, these are motifs symbolizing otherness, heresy, stupidity, insanity, and buffoonery in the stories of “The Ship of Fools”, “The Prodigal Son”, “Extraction of Stones of Folly” (Moria), and others. The roots of these motifs of laughter culture can be associated with the ancient monosandalism of the Dionysian motives of disbalance. Secondly, these are the motifs of legal symbolism — the Jewish rituals of the cession of rights (Kinyan), including the ritual of divorce in the levirate marriage (Khalitsa), respect for jurisdiction by removing the shoes before the sacred place and derivative genre motifs (for example, the regional cult of the “Joseph’s diapers”). Particular attention has been paid to the legal symbolism of divorce (Mt. 1:19) in the context of the analysis of the European divorce and the separation “a mensa et thoro” statistics in the 14th-15th centuries, reflecting the specifics of paternalistic relations in the Franco-Flemish region. Thirdly, these are other genre, erotic, folklore and literary motifs. In the form of genre details, sometimes with possible allusions to the above-mentioned meanings, these motifs are inherited in the art of the 17th century, for example, in paintings by Rembrandt, Metsyu, and Vermeer.